Sensing device based on self-driven integrated phase change material
By adopting the integrated design of phase change materials and R-TENG in metamaterial optoelectronic devices, the problem of narrow working bandwidth and real-time regulation of electromagnetic waves of metamaterial optoelectronic devices is solved, and the self-driven real-time regulation of terahertz waves is realized and the Visible light intensity modulation improves the device's frequency and amplitude modulation capabilities.
Patent Information
- Application Number
- CN202411295900.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-18
- Publication Date
- 2025-01-10
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing metamaterial optoelectronic devices have problems with narrow working bandwidth and inability to regulate electromagnetic waves in real time, and the driving scheme of self-driven optoelectronic devices has not been effectively solved.
Using a self-driven optical signal attenuator based on phase change materials and a real-time terahertz metamaterial modulator integrated with a rotary friction nanogenerator (R-TENG) to improve the output performance of TENG through electrospinning technology and combine polymer dispersed phases. The integrated design of variable materials and metamaterials with different surface structures realizes the self-driven real-time regulation of terahertz waves.
Real-time modulation of visible light intensity and self-driven real-time regulation of terahertz waves are realized, the frequency and amplitude modulation capabilities of metamaterials are improved, and the optical needs of converged plastic shaping metamaterials are met.
Smart Images

Figure CN119291948A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of self-driven phase-change photoelectric sensor devices, in particular to a self-driven photoelectric metamaterial attenuator and a self-driven real-time terahertz metamaterial spectral modulator based on phase-change materials. Background Art
[0002] Metamaterial optoelectronic devices can change the intensity, amplitude, frequency and other characteristics of electromagnetic waves during propagation by means of external field control. This characteristic makes metamaterials show great potential in the design and application of optoelectronic devices. Metamaterials are a new type of artificial electromagnetic material, composed of subwavelength unit arrays. Different array structures will produce different electromagnetic responses. Photonic resonant devices that meet the requirements of special frequency bands can be realized by designing geometric structures and sizes. This design can make the electromagnetic properties of metamaterials such as equivalent dielectric constant and equivalent magnetic permeability adjustable and controllable, and obtain electromagnetic response characteristics that are completely different from the constituent materials or other materials in nature. Typical metamaterials are composed of structural units that realize negative dielectric constant and negative magnetic permeability, mainly including unit structures such as metal wires and split ring resonators. However, since its performance is restricted by the unit structure parameters, it still has problems such as narrow working bandwidth and inability to control in real time in terms of controlling electromagnetic waves. At present, the realization of real-time control characteristics of metamaterials on electromagnetic wave amplitude, phase, etc. is a hot topic in academic and industrial research.
[0003] Phase change materials have dielectric and optical anisotropy covering a wide frequency band from ultraviolet to microwave, and their director distribution and properties respond sensitively to changes in applied external fields such as light field, electric field, magnetic field, etc. Therefore, the intensity, frequency shift, amplitude and other properties of electromagnetic waves in each frequency band can be modulated. They are rare optoelectronic functional materials that can realize regulation functions and are often used to prepare optoelectronic devices. In addition, polymer dispersed liquid crystal phase change material (PDLC) is a material mixed with phase change material and polymer. Due to its unique electrically controlled optical switching characteristics, it can be widely used in smart displays and windows.
[0004] The triboelectric nanogenerator (TENG) provides a feasible solution for driving optoelectronic devices due to its unique advantages such as high integration, long service life, and environmental friendliness. TENG can effectively collect different mechanical energy in the living environment and convert it into electrical energy and use it to continuously power various sensors, providing a new idea for building self-driven optoelectronic devices. Summary of the invention
[0005] The purpose of this application is to provide a self-driven optical signal attenuator based on phase change material metamaterials and a self-driven integrated real-time terahertz metamaterial phase change material modulator based on R-TENG, to verify that it has good output performance and spectrum tunable characteristics, and can effectively solve the problems existing in the above background.
[0006] In order to achieve the above purpose, this application adopts the following technical solutions:
[0007] A sensing device based on self-driven integrated phase change material, comprising a metamaterial optical signal attenuator and a real-time terahertz metamaterial modulator, characterized in that the metamaterial optical signal attenuator comprises: a first phase change material module, a first metamaterial module, a friction nanogenerator TENG module;
[0008] The preparation method of the first phase change material module includes: firstly, using two 2cm*3cm polyethylene terephthalate PET-indium tin oxide ITO films as transparent electrodes, and using a polyimide (PI) tape with a thickness of 50um and a width of 5mm to stick them around to prepare a phase change material box; secondly, mixing and stirring the configured phase change material E7 and the photocurable polymer NOA65 in a mass ratio of 8:2, placing the configured phase change material E7 mixture on a heating table with a constant temperature of 60°C, heating for half an hour, transferring the phase change material mixture to the PET-ITO substrate through a dropper, and then covering it with another PET-ITO, and irradiating it with a 95mW / cm2 ultraviolet lamp for 15 minutes to cure it;
[0009] The first metamaterial module preparation method includes: first depositing a layer of aluminum oxide on a clean substrate, then depositing a layer of silicon nitride on the aluminum oxide layer, then spin coating electron beam negative photoresist, and preparing a light focusing and shaping metamaterial module through electron beam lithography and etching processes; the metamaterial array is composed of nanopores of 100nm, 150nm, 200nm, 250nm and 300nm;
[0010] The preparation method of the friction nanogenerator TENG module includes: a substrate, an electrode layer, a positive friction layer and a negative friction layer; a nylon 6 nanofiber membrane is prepared by an electrospinning process to construct a friction layer nanomaterial, a 30mm*30mm aluminum film is attached to the center of a 50mm*50mm polymethyl methacrylate (PMMA) substrate as an electrode, and the nylon membrane prepared by spinning is applied to the aluminum film; then a sponge with the same size as the aluminum film is bonded to another PMMA substrate as a buffer layer, and then a polyperfluoroethylene propylene (FEP) film is bonded to the aluminum film; finally, the two PMMA substrates are connected by a spring to form a vertical contact separation friction nanogenerator CS-TENG.
[0011] Preferably, the first phase change material module produces a phase change under external stimulation conditions, thereby producing a modulation effect on the electromagnetic waves passing through it.
[0012] Preferably, the first phase change material module includes liquid crystal, VO2, and Ge2Sb2Te5 series materials.
[0013] Preferably, the first metamaterial module has the characteristics of a converging lens.
[0014] Preferably, the CS-TENG includes positive and negative friction electrodes, a buffer layer, and an electrode layer, and the upper and lower electrodes are connected by a spring.
[0015] Preferably, the real-time terahertz metamaterial modulator comprises: a second phase change material module, a second metamaterial module, and a rotary friction nanogenerator R-TENG module;
[0016] The preparation method of the second phase change material module includes: using phase change material 5CB to prepare polymer dispersed liquid crystal, using a PET-based single-layer graphene film as a transparent electrode, and then using a PI tape with a thickness of 50um and a width of 5mm to isolate the device area where the polymer dispersed liquid crystal mixture is added; secondly, taking 250mg of phase change material 5CB and 62.5mg of NOA65, mixing them completely and shaking them well, placing the prepared polymer dispersed liquid crystal mixture on a heating table with a constant temperature of 60°C, heating for half an hour, transferring the polymer dispersed liquid crystal mixture to the PET-based single-layer graphene film through a dropper, and then covering it with another PET-based single-layer graphene film, and irradiating it with a 95mW / cm2 ultraviolet lamp for 15 minutes to cure it;
[0017] The second metamaterial module includes six different metamaterial arrays, namely a cross-symmetrical surface structure array with a unit spacing of 120 μm, a cross-asymmetric surface structure array, a single open ring surface structure array, a double open ring surface structure array, and a single open ring surface structure array and a double open ring surface structure array with a unit spacing of 100 μm;
[0018] The rotary friction nanogenerator R-TENG module includes a substrate, an electrode layer, a positive friction layer and a negative friction layer; the stator and rotor of the rotary friction nanogenerator R-TENG module are used to collect the mechanical energy generated during the rotational motion; the stator is composed of 18 pairs of parallel fan-shaped copper electrodes, the copper electrodes are manufactured by printed circuit board PCB technology, and a 0.1 mm thick mica film is covered on the copper electrodes as a dielectric layer; the rotor uses acrylic plate as the substrate, and the 18 pairs of fan blades on the rotor are made of polytetrafluoroethylene PTFE and polyimide film.
[0019] Preferably, the module 2 is a liquid crystal 5CB.
[0020] Preferably, the rotary friction nanogenerator R-TENG module uses mica film and PTFE film with a large difference in electronegativity as friction materials.
[0021] Compared with the prior art, this application has the following beneficial effects:
[0022] (1) Aiming at the demand for real-time modulation of visible light intensity of focusing and shaping metamaterials, a device model based on TENG self-driven phase change material attenuator was invented and implemented. The output performance of TENG was improved by electrospinning nylon membrane to more effectively drive the phase change material attenuator. The response state of the self-driven phase change material attenuator under different electric fields was used to perform real-time light intensity modulation on the metamaterial.
[0023] (2) Invented the integration of R-TENG self-driven phase change material and terahertz metamaterial system, realizing self-driven real-time control of terahertz waves. On the basis of improving the structure of R-TENG to enhance its output performance, the polymer dispersed phase change material and metamaterials with different surface structures were integrated into the design, revealing the mechanism of the effect of the alternating electric field output by the R-TENG machine on the metamaterial phase change material, and successfully realizing real-time self-driven active tuning of the frequency and amplitude of a specific terahertz frequency band. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0025] Figure 1 This is an optical behavior diagram of a TENG-driven polymer dispersed phase change material based on electrospinning according to an embodiment of the present application.
[0026] Figure 2 This is a schematic diagram of the working principle of CS-TENG according to an embodiment of the present application.
[0027] Figure 3 Output (a) open circuit voltage (b) transferred charge (c) short circuit current of CS-TENG at different contact frequencies according to an embodiment of the present application.
[0028] Figure 4 It is a schematic diagram of a test optical path according to an embodiment of the present application.
[0029] Figure 5 This is the amplitude modulation of different color lasers when the current is 0.18A according to an embodiment of the present application: (a) green (b) red (c) blue.
[0030] Figure 6 is a schematic structural diagram of an R-TENG according to an embodiment of the present application.
[0031] Figure 7It is a schematic diagram of the working principle of R-TENG according to an embodiment of the present application.
[0032] Figure 8 Output (a) transfer charge (b) short-circuit current (c) open-circuit voltage of an R-TENG module according to an embodiment of the present application.
[0033] Fig. 9 It is a partial schematic diagram under an optical microscope of (a) a cross-symmetrical surface structure array and (b) a cross-asymmetric surface structure array repeatedly composed with a spacing of d=120 μm according to an embodiment of the present application.
[0034] Fig.10 It is a partial schematic diagram under an optical microscope of (a) a single open ring surface structure array and (b) a double open ring surface structure array repeatedly composed with a spacing of d=120 μm according to an embodiment of the present application.
[0035] Fig.11 It is a partial schematic diagram under an optical microscope of (a) a single open ring surface structure array and (b) a double open ring surface structure array repeatedly composed with a spacing of d=100 μm according to an embodiment of the present application.
[0036] Fig.12 This is a metamaterial phase change material integration method according to an embodiment of the present application.
[0037] Fig.13 It is the transmittance of the cross asymmetric surface structure in TE and TM modes respectively according to an embodiment of the present application.
[0038] Fig.14 It is the transmittance of the terahertz signal under the TE wave of the cross asymmetric surface structure on the metamaterial phase change material modulator according to one embodiment of the present application.
[0039] Explanation of the reference numerals: 1-PMMA substrate; 2-sponge; 3-electrospun nylon membrane; 4-FEP membrane; 5-PET membrane; 6-ITO membrane, 7-phase change material liquid crystal E7; 8-metamaterial module; 61-rotor; 62-blade; 63-stator; 91-glass substrate pyrex7740; 92-metamaterial array; 93-PET membrane; 94-graphene; 95-phase change material liquid crystal 5CB. DETAILED DESCRIPTION
[0040] In order to make the purpose, technical solution and advantages of the present application more clearly understood, the present application is further described in detail below in conjunction with the accompanying drawings and specific embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and do not constitute a limitation to the present application.
[0041] In the following description, specific details such as specific system structures, technologies, etc. are provided for the purpose of illustration rather than limitation, so as to provide a thorough understanding of the embodiments of the present application. However, it should be clear to those skilled in the art that the present application may also be implemented in other embodiments without these specific details. In other cases, detailed descriptions of well-known systems, devices, circuits, and methods are omitted to prevent unnecessary details from obstructing the description of the present application.
[0042] Those skilled in the art will appreciate that, unless expressly stated otherwise, the singular forms "a", "an", "said" and "the" used herein may also include plural forms. It should be further understood that the term "comprising" used in the specification of the present application refers to the presence of the features, integers, steps, operations, elements and / or components, but does not exclude the presence or addition of one or more other features, integers, steps, operations, elements and / or groups thereof. It should be understood that "connected" or "coupled" used herein may include wireless connections or couplings, and the term "and / or" used includes any unit and all combinations of one or more associated listed items.
[0043] The embodiments of the present application are described in detail below, and examples of the embodiments are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements having the same or similar functions. The embodiments described below by the accompanying drawings are exemplary and are only used to explain the present application, and cannot be interpreted as limiting the present application.
[0044] It will be understood by those skilled in the art that, unless otherwise defined, all terms (including technical and scientific terms) used herein have the same meaning as those generally understood by those skilled in the art to which this application belongs. It should also be understood that terms such as those defined in common dictionaries should be understood to have meanings consistent with the meanings in the context of the prior art, and will not be interpreted with idealized or overly formal meanings unless defined as herein.
[0045] References to "one embodiment" or "some embodiments" etc. described in this application mean that a particular feature, structure or characteristic described in conjunction with the embodiment is included in one or more embodiments of the present application. Thus, the phrases "in one embodiment", "in some embodiments", "in some other embodiments", "in some other embodiments", etc. that appear at different places in this specification do not necessarily all refer to the same embodiment, but mean "one or more but not all embodiments", unless otherwise specifically emphasized in other ways. The terms "including", "comprising", "having" and their variations all mean "including but not limited to", unless otherwise specifically emphasized in other ways.
[0046] refer to Figure 1 and Figure 2 As shown, an embodiment of the present application provides an optical behavior diagram of a TENG-driven polymer dispersed phase change material based on electrospinning.
[0047] In some embodiments, the electrode material of the electrode layer 1 of the TENG in the example of the present application is a material with good conductivity, which can be metal, metal alloy, conductive fabric, etc.
[0048] In some embodiments, the positive friction layer 3 of the TENG module in the present application example can be one or more of aluminum, copper, nylon, acrylic resin, polyurethane, gold, nanofiber, wood, paper, polyoxymethylene, polyamide nylon, indium tin oxide, polyethylene glycol succinate, latex, carbon black / carbon nanotubes, styrene-acrylonitrile copolymer, textiles, graphene, aniline formaldehyde resin, chitosan-glycerol, silk, steel, etc. In a specific embodiment of the present application, the material of the positive friction layer 3 is: electrospun nylon film. And the material of the positive friction layer 3 is made by electrospinning technology, and has a higher specific surface area and surface charge density.
[0049] In some embodiments, the negative friction layer 4 of TENG in the present application example can be one or more materials such as polyperfluoroethylene propylene, polytetrafluoroethylene, polydimethylsiloxane, fluorinated ethylene propylene, polyvinylidene fluoride, polyolefin, styrene, polyester, silica gel, bacterial nanocellulose, sodium alginate, cellulose nitrate, graphene, acrylic resin, rubber, polyvinyl alcohol, etc. In a specific embodiment of the present application, the material of the negative friction layer 4 is: polyperfluoroethylene propylene (FEP) film.
[0050] In some embodiments, the phase change material 7 in the present application example can be one or more of VO2, Ge2Sb2Te5 series materials, etc. In a specific embodiment of the present application, the phase change material is liquid crystal.
[0051] In the embodiments of the present application, the materials and structures are optimized with the goal of improving the output performance and utilizing the electrical controllability of the E7 liquid crystal and the unique electromagnetic response of the metamaterial.
[0052] In the embodiment of the present application, the electrical controllability of the phase change material E7 liquid crystal and the unique electromagnetic response of the metamaterial are used as the real-time self-driven control goal of the metamaterial. The nano-metamaterial is composed of a circular hole array with a diameter of 100nm to 300nm prepared by electron beam lithography technology; and, the present application aims to improve the output performance. The positive friction layer 3 of the TENG module 3 is constructed by electrospinning technology to improve the friction characteristics of the material.
[0053] To facilitate understanding of the present application, the present application is further explained below with reference to specific embodiments in conjunction with the accompanying drawings, and the specific embodiments do not constitute a limitation on the embodiments of the present application. Those skilled in the art should understand that the accompanying drawings are only schematic diagrams of the embodiments, and the components in the accompanying drawings are not necessarily required to implement the present application. The structural, methodological, or functional changes made by ordinary technicians in the field according to the embodiments are all included in the protection scope of the present application.
[0054] Embodiment 1
[0055] like Figure 1 As shown, the metamaterial optical signal attenuator includes: a first phase change material module, a first metamaterial module 8, and a friction nanogenerator TENG module. The preparation method of the first phase change material module includes: first, two 2cm*3cm polyethylene terephthalate PET-indium tin oxide ITO films 6 are used as transparent electrodes, and a polyimide (PI) tape with a thickness of 50um and a width of 5mm is used to paste the four sides to prepare a phase change material box; secondly, the configured phase change material 7 (liquid crystal E7) and the photocurable polymer NOA65 are mixed and stirred at a mass ratio of 8:2, and the configured phase change material 7 (liquid crystal E7) mixture is placed on a heating table with a constant temperature of 60°C. After heating for half an hour, the phase change material mixture is transferred to the PET-ITO substrate through a dropper, and then covered with another PET-ITO, and 95mW / cm 2 UV light for 15 minutes to cure it.
[0056] The preparation method of the first metamaterial module 8 includes: first depositing a layer of aluminum oxide on a clean substrate, then depositing a layer of silicon nitride on the aluminum oxide layer, and then spin-coating electron beam negative photoresist, and preparing a light focusing and shaping metamaterial module through electron beam lithography and etching processes; the metamaterial array is composed of nanopores of 100nm, 150nm, 200nm, 250nm and 300nm;
[0057] The preparation method of the friction nanogenerator TENG module includes: a substrate, an electrode layer, a positive friction layer and a negative friction layer; a nylon 6 nanofiber membrane is prepared by an electrospinning process to construct a friction layer nanomaterial, a 30mm*30mm aluminum film is attached to the center of a 50mm*50mm polymethyl methacrylate (PMMA) substrate as an electrode, and the nylon membrane prepared by spinning is applied to the aluminum film; then a sponge with the same size as the aluminum film is bonded to another PMMA substrate as a buffer layer, and then a polyperfluoroethylene propylene (FEP) film is bonded to the aluminum film; finally, the two PMMA substrates are connected by a spring to form a vertical contact separation friction nanogenerator CS-TENG.
[0058] like Figure 1As shown, a 30mm*30mm aluminum film is attached to the center of a 50mm*50mm PMMA substrate 1 as an electrode. The nylon film material 3 is then trimmed, and the nylon film 3 is attached to the aluminum film using double-sided tape as an adhesive material. A sponge 2 having the same size as the aluminum film is then bonded to another PMMA substrate as a buffer layer. At the same time, another friction material FEP film 4 is bonded to the aluminum film. Finally, the two PMMA substrates 1 are connected by spring support to form a CS-TENG. When the upper PMMA substrate 1 is repeatedly pressed, the TENG will output a stable alternating current, which can be used to drive the polymer dispersed phase change liquid crystal material to present an open state.
[0059] like Figure 2 As shown in Figure 1, CS-TENG can spontaneously introduce static charge through contact. The preparation method of the device is simple, and the cost can be controlled by the selection of materials. Since nylon membrane has many advantages such as lightness, breathability, stretchability, stable output, high sensitivity, good durability, and easy to lose electrons, electrospun nylon membrane is selected to be combined with FEP to form a triboelectric pair. The initial state is shown in Figure (a). At this time, the positive and negative materials are in contact. Due to the difference in electronegativity, the nylon electrospun membrane is positively charged, while the FEP is negatively charged. When the nylon spinning membrane is away from the FEP, as shown in Figure (b), the electric field balance constructed between the two is broken. In order to balance the potential difference, electrons will flow from the lower electrode to the upper electrode through the external circuit. Figure (c) shows that the distance between the positive and negative triboelectric materials is the farthest. At this time, it is in a critical equilibrium state. The charge carried by the triboelectric material is balanced by the charge of each other's back electrodes. As shown in Figure (d), when a force is applied to make the nylon membrane close to the FEP again, in order to balance the potential difference, electrons will flow from the upper electrode to the lower electrode. This cycle is repeated to produce a stable and reliable AC output.
[0060] like Figure 3 As shown in Figure 1, when the contact force is 10N and the frequency increases from 1Hz to 5Hz in steps of 1Hz, the open circuit voltage of TENG remains basically unchanged, with a peak-to-peak value of about 165V, or an effective value of 116.7V. This is because there is no dynamic charge transfer process in the open circuit state. During this process, the friction charge density and separation distance hardly change, so the open circuit voltage is relatively stable. Similarly, as shown in Figure (b), the transferred charge remains basically unchanged, at about 86nC. The short-circuit current is different. Its peak-to-peak value has a significant increasing trend with the increase of frequency. In this process, it increases from 3μA to 25μA, that is, the effective value increases from 2.1μA to 17.7μA, as shown in Figure (c), indicating that TENG has better power conversion efficiency at higher frequencies.
[0061] like Figure 4As shown in the figure, the tested optical components mainly include a laser light source with wavelengths of 450nm, 532nm and 633nm, a self-driven phase change material attenuation module, a convergence shaping metamaterial module and an optical power meter (PPM350-100-USB). The electrical adjustability of the phase change material attenuator is the key to achieving real-time modulation of optical power. When CS-TENG provides voltage to the phase change material attenuator, the arrangement of the phase change material molecules changes, thereby changing its transmittance to visible light. CS-TENG provides sufficient AC voltage to the attenuator test system to switch the phase change material between the on and off states. By changing the dielectric properties of the phase change material, the electrical adjustability of the attenuator is achieved, and combined with the unique electromagnetic response of the metamaterial, the real-time modulation effect of the optical power is achieved. The modulated light beam is received by the power meter to measure and record the changes in optical power. This modulation effect is not only highly flexible and adjustable, but also can meet the requirements of fast response.
[0062] like Figure 5 As shown, the amplitude modulation under different color lasers when the current is 0.18A (a) green (b) red (c) blue.
[0063] The real-time terahertz metamaterial modulator includes: a second phase change material module, a second metamaterial module, and a rotary friction nanogenerator R-TENG module; the preparation method of the second phase change material module includes: using phase change material 5CB to prepare polymer dispersed liquid crystal, using a PET-based single-layer graphene film as a transparent electrode, and then using a PI tape with a thickness of 50um and a width of 5mm to isolate the device area where the polymer dispersed liquid crystal mixture is added; secondly, 250mg of phase change material 5CB and 62.5mg of NOA65 are taken and mixed completely and shaken, and the prepared polymer dispersed liquid crystal mixture is placed on a heating table with a constant temperature of 60°C. After heating for half an hour, the polymer dispersed liquid crystal mixture is transferred to the PET-based single-layer graphene film through a dropper, and then covered with another PET-based single-layer graphene film, and 95mW / cm 2 UV light for 15 minutes to cure it.
[0064] The rotary friction nanogenerator R-TENG module includes a substrate, an electrode layer, a positive friction layer and a negative friction layer; the stator and rotor of the rotary friction nanogenerator R-TENG module are used to collect the mechanical energy generated during the rotational motion; the stator is composed of 18 pairs of parallel fan-shaped copper electrodes, which are manufactured using printed circuit board PCB technology and covered with a 0.1 mm thick mica film as a dielectric layer; the rotor uses acrylic board as the substrate, and the 18 pairs of fan blades on the rotor are made of polytetrafluoroethylene PTFE and polyimide film.
[0065] like Figure 6 As shown. The R-TENG consists of a stator 63 and a rotor 61, which are used to collect the mechanical energy generated during the rotational motion. The stator part is composed of 18 pairs of parallel fan-shaped copper electrodes, which are manufactured by PCB technology and covered with a 0.1mm thick mica film as a dielectric layer. The rotor part uses a sturdy and durable acrylic plate as a substrate to ensure its stability and durability during long-term rotation. The 18 pairs of blades 62 on the rotor are made of PTFE and Kapton films. The invention of the present invention uses mica film and PTFE film with a large difference in electronegativity as friction materials, which is conducive to improving the output performance of R-TENG. In addition, after careful design and calculation, the shapes and sizes of these PTFE films and Kapton films are made to ensure that each PTFE film has the most effective contact with the mica film during rotation, thereby improving the AC output performance of the R-TENG.
[0066] like Figure 7 As shown. The working principle is as follows. In the initial state, as shown in Figure (a), the contact area of the PTFE film is half of that of the mica film, so the positive charge density of the mica film is twice the negative charge density of the PTFE. When the rotor rotates counterclockwise, as shown in Figure (b), the PTFE film overlaps with the copper (Cu) electrode on the left. Due to electrostatic induction, the left and right Cu electrodes will generate equal amounts of positive and negative charges respectively. When the PTFE film slides counterclockwise, in order to eliminate the potential difference between the left and right copper electrodes during this rotation process, the negative charge will flow from the right Cu electrode to the left Cu electrode. As shown in Figure (c), when the PTFE film continues to rotate until it completely overlaps with the right Cu electrode, in order to balance the potential difference, the electrons on the right Cu electrode will flow to the left Cu electrode. Similarly, as shown in Figure (d), when the next PTFE dielectric film reaches the left Cu electrode, the electrons on the left Cu electrode flow to the right Cu electrode again. In this way, during the rotation of the rotor, the above electron transfer process occurs repeatedly to form a stable AC output.
[0067] like Figure 8 As shown in the figure, the performance of the R-TENG is tested by changing its rotation speed while other conditions remain unchanged. When the rotation speed increases from 50rpm to 250rpm in steps of 50, the transfer charge of the R-TENG increases from 63nC to 100nC, the peak-to-peak value of the short-circuit current increases from 14.5μA to 80μA, and the effective value increases from 10.3μA to 56.6μA, while the peak-to-peak value of the open-circuit voltage increases from 115V to 180V, and the effective value increases from 81.3V to 127.3V. When the speed exceeds 250rpm, the output of the R-TENG tends to a stable value.
[0068] The second metamaterial module includes: six different metamaterial arrays according to the metamaterial microstructure and the spacing between microstructure units, namely, a cross-symmetrical surface structure array composed of microstructure units repeated at a spacing of 120μm, a cross-asymmetric surface structure array, a single open ring surface structure array, a double open ring surface structure array, and a single open ring surface structure array and a double open ring surface structure array composed of microstructure units repeated at a spacing of 100μm.
[0069] Fig. 9 1 and 2 are partial schematic diagrams under an optical microscope of (a) a cross-symmetrical surface structure array and (b) a cross-asymmetric surface structure array repeatedly composed of a spacing of d=120 μm according to an embodiment of the present application.
[0070] Fig.10 Shown are partial schematic diagrams under an optical microscope of (a) a single open ring surface structure array and (b) a double open ring surface structure array repeatedly composed with a spacing of d=120 μm according to an embodiment of the present application.
[0071] Fig.11 Shown are partial schematic diagrams under an optical microscope of (a) a single open ring surface structure array and (b) a double open ring surface structure array repeatedly composed with a spacing of d=100 μm according to an embodiment of the present application.
[0072] like Fig.12 As shown, the metamaterial surface structure and phase change material are designed to match, the phase change material box slot is 2cm*3cm, and the thickness is 0.85mm. The metamaterial phase change material integration method is to sequentially attach the glass substrate 91 (pyrex7740), metamaterial array 92, PET film 93, graphene 94, phase change material 95 (liquid crystal 5CB), graphene 94, and PET film 93 in the upper and lower order.
[0073] like Fig.13 As shown in the figure, in the TE mode, the main resonance frequencies are at 0.131THz, 0.174THz and 0.216THz, and the transmittances are 0.785, 0.575 and 0.335 respectively. In the TM mode, the blue shifts to 0.134THz, 0.181THz and 0.222THz, and the transmittances at these three locations also change compared to the TE mode, becoming 0.791, 0.565 and 0.412 respectively.
[0074] like Fig.14 As shown, before and after the action of the R-TENG metamaterial phase change device at 0.144 THz, the transmittance increased from 0.336 to 0.351, and the amplitude modulation depth was 4.5%.
[0075] In the description of the present application, it should be understood that the symbols such as parameters and variables mentioned in the embodiments of the present application can be replaced by any other codes that will not cause confusion.
[0076] In the description of the present application, it should be understood that the terms "middle", "longitudinal", "lateral", "length", "width", "thickness", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", etc., indicating orientations or positional relationships, are based on the orientations or positional relationships shown in the accompanying drawings, and are only for the convenience of describing the present application and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be understood as a limitation on the present application.
[0077] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated. Thus, the features defined as "first" and "second" may explicitly or implicitly include at least one of the features.
[0078] In this application, unless otherwise clearly specified and limited, the terms "installed", "connected", "connected", "fixed" and the like should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection or an indirect connection through an intermediate medium, it can be the internal connection of two elements or the interaction relationship between two elements, unless otherwise clearly defined. For ordinary technicians in this field, the specific meanings of the above terms in this application can be understood according to specific circumstances.
[0079] In the present application, unless otherwise clearly specified and limited, a first feature being “above” or “below” a second feature may mean that the first and second features are in direct contact, or the first and second features are in indirect contact through an intermediate medium. Moreover, a first feature being “above”, “above”, and “above” a second feature may mean that the first feature is directly above or obliquely above the second feature, or simply means that the first feature is higher in level than the second feature. A first feature being “below”, “below”, and “below” a second feature may mean that the first feature is directly below or obliquely below the second feature, or simply means that the first feature is lower in level than the second feature.
[0080] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present application. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.
[0081] The above is only a preferred specific implementation of the present application, but the protection scope of the present application is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed in the present application should be included in the protection scope of the present application. Therefore, the protection scope of the present application should be based on the protection scope of the claims.
Claims
1. A sensing device based on self-driven integrated phase change material, comprising a metamaterial optical signal attenuator and a real-time terahertz metamaterial modulator, characterized in that: The metamaterial optical signal attenuator comprises: a first phase change material module, a first metamaterial module, and a friction nanogenerator TENG module; The preparation method of the first phase change material module includes: firstly, using two 2cm*3cm polyethylene terephthalate PET-indium tin oxide ITO films as transparent electrodes, and using a polyimide (PI) tape with a thickness of 50um and a width of 5mm to stick them around to prepare a phase change material box; secondly, mixing and stirring the configured phase change material E7 and the photocurable polymer NOA65 in a mass ratio of 8:2, placing the configured phase change material E7 mixture on a heating table with a constant temperature of 60°C, and after heating for half an hour, transferring the phase change material mixture to the PET-ITO substrate through a dropper, and then covering it with another PET-ITO, and using 95mW / cm 2 Irradiate with UV light for 15 minutes to cure it; The first metamaterial module preparation method includes: first depositing a layer of aluminum oxide on a clean substrate, then depositing a layer of silicon nitride on the aluminum oxide layer, then spin coating electron beam negative photoresist, and preparing a light focusing and shaping metamaterial module through electron beam lithography and etching processes; the metamaterial array is composed of nanopores of 100nm, 150nm, 200nm, 250nm and 300nm; The preparation method of the friction nanogenerator TENG module includes: a substrate, an electrode layer, a positive friction layer and a negative friction layer; a nylon 6 nanofiber membrane is prepared by an electrospinning process to construct a friction layer nanomaterial, a 30mm*30mm aluminum film is attached to the center of a 50mm*50mm polymethyl methacrylate (PMMA) substrate as an electrode, and the nylon membrane prepared by spinning is applied to the aluminum film; then a sponge with the same size as the aluminum film is bonded to another PMMA substrate as a buffer layer, and then a polyperfluoroethylene propylene (FEP) film is bonded to the aluminum film; finally, the two PMMA substrates are connected by a spring to form a vertical contact separation friction nanogenerator CS-TENG.
2. The sensing device based on self-driven integrated phase change material according to claim 1, characterized in that: The first phase change material module undergoes phase change under external excitation conditions, producing a modulation effect on the electromagnetic waves passing through it.
3. The sensing device based on self-driven integrated phase change material according to claim 1, characterized in that: The first phase change material module includes liquid crystal, VO2, and Ge2Sb2Te5 series materials.
4. The sensing device based on self-driven integrated phase change material according to claim 1, characterized in that: The first metamaterial module has the characteristics of a converging lens.
5. The sensing device based on self-driven integrated phase change material according to claim 1, characterized in that: The CS-TENG includes positive and negative friction electrodes, a buffer layer, and an electrode layer, and the upper and lower electrodes are connected by springs.
6. The sensing device based on self-driven integrated phase change material according to claim 1, characterized in that: The real-time terahertz metamaterial modulator comprises: a second phase change material module, a second metamaterial module, and a rotary friction nanogenerator R-TENG module; The preparation method of the second phase change material module includes: using phase change material 5CB to prepare polymer dispersed liquid crystal, using a PET-based single-layer graphene film as a transparent electrode, and then using a PI tape with a thickness of 50um and a width of 5mm to isolate the device area where the polymer dispersed liquid crystal mixture is added; secondly, taking 250mg of phase change material 5CB and 62.5mg of NOA65, mixing them completely and shaking them well, placing the prepared polymer dispersed liquid crystal mixture on a heating table with a constant temperature of 60°C, heating for half an hour, transferring the polymer dispersed liquid crystal mixture to the PET-based single-layer graphene film through a dropper, and then covering it with another PET-based single-layer graphene film, and using 95mW / cm 2 Irradiate with UV light for 15 minutes to cure it; The second metamaterial module includes six different metamaterial arrays, namely a cross-symmetrical surface structure array with a unit spacing of 120 μm, a cross-asymmetric surface structure array, a single open ring surface structure array, a double open ring surface structure array, and a single open ring surface structure array and a double open ring surface structure array with a unit spacing of 100 μm; The rotary friction nanogenerator R-TENG module includes a substrate, an electrode layer, a positive friction layer and a negative friction layer; the stator and rotor of the rotary friction nanogenerator R-TENG module are used to collect the mechanical energy generated during the rotational motion; the stator is composed of 18 pairs of parallel fan-shaped copper electrodes, the copper electrodes are manufactured by printed circuit board PCB technology, and a 0.1 mm thick mica film is covered on the copper electrodes as a dielectric layer; the rotor uses acrylic plate as the substrate, and the 18 pairs of fan blades on the rotor are made of polytetrafluoroethylene PTFE and polyimide film.
7. The sensing device based on self-driven integrated phase change material according to claim 6, characterized in that: The module 2 is a liquid crystal 5CB.
8. The sensing device based on self-driven integrated phase change material according to claim 6, characterized in that: The rotary friction nanogenerator R-TENG module uses a mica film and a PTFE film with a large difference in electronegativity as friction materials.
Citation Information
Patent Citations
Self-driven optical switch and wireless sensing system
CN111487802A
Dielectric medium trap state measuring and imaging system and method driven by friction nanometer generator
CN113281380A
Preparation method of friction nano-generator based on three-dimensional multilayer film structure composite electrode
CN114826015A
Wave sensing system based on triboelectric driving liquid crystal
CN117470200A
Asymmetric transmission multi-focus convergence metasurface lens suitable for terahertz frequency band and preparation method of asymmetric transmission multi-focus convergence metasurface lens
CN118399089A